Two‐Dimensional Si Nanosheets with Local Hexagonal Structure on a MoS2 Surface. (17th December 2013) - Chiappe, Daniele; Scalise, Emilio; Cinquanta, Eugenio; Grazianetti, Carlo; van den Broek, Bas; Fanciulli, Marco; Houssa, Michel; Molle, Alessandro
<x xml:space="preserve">Abstract</x> The structural and electronic properties of a Si nanosheet (NS) grown onto a MoS2 substrate by means of molecular beam epitaxy are assessed. Epitaxially grown Si is shown to adapt to the trigonal prismatic surface lattice of MoS2 by forming two‐dimensional nanodomains. The Si layer structure is distinguished from the underlying MoS2 surface structure. The local electronic properties of the Si nanosheet are dictated by the atomistic arrangement of the layer and unlike the MoS2 hosting substrate they are qualified by a gap‐less density of states. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>